NEW OPPORTUNITIES FOR PREVENTIVE THERAPY WITH STATINS DURING CHD PATIENTS’ REHABILITATION, WITH CLINICAL SIGNS OF MODERATE CHF: EFFECTIVENESS OF ROSUVASTATIN AND EZETIMIBE - N. I. Tarasov; M. N. Sinkova; L. K. Isakov; N. B. Lebedeva; V. A. Shilov; A. T. Teplyakov (Кардиоваскулярная терапия и профилактика)
Aim. To study the efficacy of rosuvastatin and ezetimibe combination in patients with moderate clinical signs of chronic heart failure.Material and methods. We incllded outpatients (n=70) >40 y.o. with clinical picture of moderate heart failure (functional class by NYHA II), with comorbid diabetes 2 type, carotid atherosclerosis and hypercholesterolemia. Patients were randomized to 2 groups, 35 persons in each. In the 1st group threatment was performed with rosuvastatin 20 mg daily, with ezetimibe 20 mg daily, in the 2nd — only rosuvastatin 20 mg daily. During one year of study we collected primary endpoints: death, myocardial infarction, stroke, hospitalizations; and secondary endpoints: the amount of those reached target level of low density lipoproteides cholesterol (LDL), changes of lipidogram, C-reactive protein (CRP), intima-media thickness of internal carotid artery.Results. Significant decrease of LDL comparing to baseline, occured in both groups by the end of the first month and remained until the end of study. The most significant LDL decrease (mediana >50%) occured in 1st group by 12 months of the study. Also, since the 3 month, we observed the decrease of LDL more than 45%. In the 2nd group this parameter was not more than 40%. The decrease of CRP by 12 months of the study was found only in the 1st group: mediana of baseline value 3,2 mg/L, end of study mediana 2,2 mg/L, mediana of changes 31,25% (p=0,028). Hospitalizations related to cardiovascular diseases were at level 14,3% in 1 group, and 40% in the 2nd st (р=0,032).Conclusion. Prescription of combination hypolipidemic therapy by rosuvastatin and ezetimibe at dose 20 mg/daily leads to more prominent decrease of LDL in blood, decrease of CRP, number of hospitalizations for cardiovascular diseases comparing to single use of rosuvastatin 20 mg/daily.